Gallbladder cancer detected by elevated serum KL-6 levels during the follow-up of interstitial pneumonia: a case report - Yonenaga, Yoshikuni (Int Cancer Conf J, 2021)
Serum Krebs von den Lungen-6 (KL-6) is clinically used for the diagnosis of interstitial pneumonia (IP) as well as the evaluation of its disease activity. A female patient was diagnosed with idiopathic IP when she was 62 years old. Four years later, serum levels of KL-6 had been elevated gradually from 2400–3821 U/ml, and she was found to have gallbladder cancer detected by contrast-enhanced computed tomography (CT) and (18)F-fluorodeoxyglucose (FDG)-positron emission tomography (PET)/CT. She thus underwent a radical extended cholecystectomy. After the operation, serum levels of KL-6 showed a steep decline to 590 U/ml. Immunohistological examination revealed that KL-6 presented in gallbladder cancer cells. Taken together, serum KL-6 was shown to be produced by gallbladder cancer cells. Here, we present the first patient in whom increased serum KL-6 levels led to the diagnosis of gallbladder cancer during follow-up of IP. When serum levels of KL-6 are elevated during the follow-up care of IP despite no worsening of IP, an examination of the whole body should be performed to find possibly existing malignant tumors.